Investigating vertical charge plasma tunnel field effect transistors beyond semiclassical assumptions - Cherik, Iman Chahardah; Mohammadi, Saeed; Hurley, Paul K.; Ansari, Lida; Gity, Farzan (Scientific reports, 2025)
In this paper, we examine the effects of subband quantization on the efficacy of an L-shaped gate vertical dopingless tunneling field-effect transistor. The proposed architecture leverages an intrinsic tunneling interface that is fully aligned with the gate metal, resulting in enhanced electrostatic control. We utilized a two-step numerical simulation approach grounded in the Schrödinger-Poisson equations to evaluate the performance of our proposed device and accurately calculate the ON-state current. Additionally, we assessed the influence of defects at the heterojunction on the performance of our device. Under quantum mechanical assumptions, parameters such as I ON = 23.8 µA/µm, SS AVG = 12.03 mV/dec, and the I ON / I OFF ratio = 4.88 × 10 10 indicate that our structure is a promising candidate for high-performance applications.